2021
DOI: 10.18844/gjcs.v11i1.5030
|View full text |Cite
|
Sign up to set email alerts
|

The significance of typography in data visualization

Abstract: With the development of technology and the dominance of the digital world, typography has become a critical issue. Information design systems are considered as one of the significant areas of graphic design and big data provides essential information on data visualization. This research aims to analyse the effects of typographic elements on visualizing data in terms of visual communication, by discussing the value that typography gives to design space. The research discusses randomly selected 10 infographic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Turkkan found that typesetting elements greatly impacted the design effect in the process of IV design. The design considering typesetting was visually more attractive and preferable than other designs [5]. Yang et al designed a big data analytics (BDA) and multidimensional IV platform astronomical data analysis (DA), which provided strong technical support for astronomical research topics, such as astronomical image processing (IP), moving target extraction, space target orbit calculation, numerical cosmology, cosmological simulation, and galaxy fluid simulation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Turkkan found that typesetting elements greatly impacted the design effect in the process of IV design. The design considering typesetting was visually more attractive and preferable than other designs [5]. Yang et al designed a big data analytics (BDA) and multidimensional IV platform astronomical data analysis (DA), which provided strong technical support for astronomical research topics, such as astronomical image processing (IP), moving target extraction, space target orbit calculation, numerical cosmology, cosmological simulation, and galaxy fluid simulation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the standard SQL language in relational databases makes it possible to perform the same actions on different DBMS, executing identically formed queries. Thus, nowadays correctly designed information systems can be ported between several DBMS [8][9][10][11]. The problems of restricting access to individual records are arising increasingly in connection with the growing need for flexibility in restricting access in modern databases, including when using them to store information classified as state or commercial secrets.…”
Section: Introductionmentioning
confidence: 99%